Ecopreneurship, rent-seeking, and free-riding in global context: Job-creation without ecocide. Issue 1 (2nd January 2016) - Isaak, Robert
Abstract : As a species, human beings are free-riders incentivized to adopt 'rational' short-term measures that assure long-term ecocide given increasing uncertainty due to the increasing speed of high-tech powered globalization. The financial crisis and displacement of employment by technological advances reinforce momentary opportunism. Policy-makers often frame ecopreneurship as a short-term solution for creating 'green jobs', with the potential to alleviate the environmental and unemployment crises simultaneously. Globalization has resulted in increasing public uncertainty and anxiety challenging overwhelmed state budgets and requiring supplementary individual investments. Understandable short-term 'rent-seeking' must be co-opted by firm green public policies transforming unbridled 'casino capitalism' into a regulated 'green casino', channeling inevitable human speculation and free-rider behavior toward sustainability. Ecopreneurship in this context is a Sisyphus 'green-green' job-creating process, a realistic, existential effort to head off the most egregious negative forms of entropy in order to delay or avert such collective suicide a bit longer.